2021
DOI: 10.1155/2021/5596384
|View full text |Cite
|
Sign up to set email alerts
|

Financial Crisis Early Warning Based on Panel Data and Dynamic Dual Choice Model

Abstract: Based on the research of currency crisis pressure index, bank crisis pressure index, and asset bubble crisis pressure index, this paper introduces an external shock pressure index reflecting the impact of global economic changes on economy and synthesizes systemic financial crisis pressure based on the above four pressure indexes; then, all the alternative early warning indicators and the systemic risk pressure index constructed in this paper were tested for Granger causality. We build financial systemic risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Comparably, the AUC and distance to corner also show that credit-to-GDP gap outperforms Non-performing loans, loan to deposit ratio and asset prices as EWIs of financial crisis no matter which filter was used. This result supports several earlier studies including Du [5], Sally and Katsiaryna [6] for advanced economies, Drehmann and Yetman [3], Beutel, List and Schweinitz [44], Giordani and Simon [45], Geršl, and Jašová [46] among others. However, the result of the present study is at variant with Sally and Katsiaryna [6] whose study indicated that asset prices do better for emerging economies and Ihejirika [4] whose findings show that Creditto-GDP Gap performs poorly in Nigeria.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 4 more Smart Citations
“…Comparably, the AUC and distance to corner also show that credit-to-GDP gap outperforms Non-performing loans, loan to deposit ratio and asset prices as EWIs of financial crisis no matter which filter was used. This result supports several earlier studies including Du [5], Sally and Katsiaryna [6] for advanced economies, Drehmann and Yetman [3], Beutel, List and Schweinitz [44], Giordani and Simon [45], Geršl, and Jašová [46] among others. However, the result of the present study is at variant with Sally and Katsiaryna [6] whose study indicated that asset prices do better for emerging economies and Ihejirika [4] whose findings show that Creditto-GDP Gap performs poorly in Nigeria.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…This study focuses on asset prices, Non-Performing Loans and Loan to Deposit Ratio. The literature on credit-to-GDP ratio and the derived gap has received much attention from scholars [1,2,3,4,5,6] among others).…”
Section: Early Warning Indicators (Ewis)mentioning
confidence: 99%
See 3 more Smart Citations